THE IMPACT OF THE INDONESIA SMART CARD (KIP) ASSISTANCE ON THE LEARNING MOTIVATION AND ACADEMIC ACHIEVEMENT OF PESANTREN ALUMNI - Muhammad Tri Gunawan; Hasnil Aida (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to determine the impact of the Indonesian Smart Card (KIP) assistance program on the learning motivation and academic achievement of alumni of Mawaridussalam Islamic Boarding School in Deli Serdang. This research is motivated by the importance of educational assistance in supporting the continuity of education for students from underprivileged families. The KIP assistance program is expected not only to help fulfill educational financial needs but also to improve learning motivation and academic achievement among pesantren alumni. This study employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of KIP recipient alumni, pesantren administrators, and other related parties. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation and method triangulation techniques. The results of the study indicate that the KIP assistance program has a positive impact on the learning motivation and academic achievement of alumni of Mawaridussalam Islamic Boarding School in Deli Serdang. The assistance helped alumni fulfill educational needs such as tuition fees, books, transportation, and other academic necessities. In addition, the KIP program increased students’ enthusiasm for learning, discipline, and self-confidence in continuing their education. In terms of academic achievement, most alumni experienced improvement in academic performance and were able to complete their studies more successfully. However, family environment, pesantren support, and individual abilities also influenced the academic success of the alumni. This study concludes that the KIP assistance program plays an important role in improving learning motivation and academic achievement among pesantren alumni. Therefore, educational assistance programs should continue to be improved and accompanied by sustainable guidance in order to provide more optimal benefits for students from underprivileged families